Older people's views on what they need to successfully adjust to life with a hearing aid - Kelly, Timothy B (Blackwell Publishing Ltd, 2013)
This article reports a study exploring what older people believe would enable them to adjust to and gain maximum benefit from wearing a hearing aid. A mixed methods approach was employed during 2006 involving interviews with key stakeholders, a survey across three Scottish health board areas and focus groups. Nine key stakeholders from six national and local organisations were interviewed about the needs of older people being fitted with hearing aids. In total, 240 older people belonging to three different types of hearing impaired older people were surveyed: long-term users of hearing aids, new hearing aid users, and those on a waiting list from urban and rural areas (response rate = 24%). A series of eight follow-up focus groups with 31 audiology patients was held. Health professionals appeared to neglect appropriate provision of information and overly rely on technological interventions. Of 154 older people already fitted with hearing aids, only 52% of hearing aid users reported receiving enough practical help post fitting and only 41% reported receiving enough support. Approximately 40% reported not feeling confident in the use of their aids or their controls. Older people wanted more information than they received both before and after hearing aid fitting. Information provision and attention to the psychosocial aspects of care are key to enabling older people to adjust and optimise hearing aid benefit.